The Optimal Axial Anatomical Site for a Single-Slice Area to Quantify the Total Volume of Visceral Adipose Tissue in Quantitative CT - Chen, Sihui; Ma, Duoshan; Su, Danyang; Li, Yali; Yu, Xi; Jiang, Yaojun; Gao, Jianbo; Wu, Yan (Frontiers in Endocrinology, 2022)
Purpose: Determine the association between cross-sectional visceral adipose tissue (VAT) area of different anatomic locations and total abdominopelvic VAT volume; identify the optimal measurement site in a single-slice to quantify the total VAT volume. Method: Participants who underwent non-contrast abdominal scan by quantitative CT (QCT) were enrolled from May 2021 to October 2021. The VAT area (cm2) at different anatomic sites as upper-pole, lower-pole, and hilum of the kidney, intervertebral disc of L2/L3 and L5/S1, and umbilical level were measured on QCT PRO BMD workstation (Mindways QCT PRO workstation). The total VAT volume (cm3) from the upper pole of kidney to the L5/S1 intervertebral disc of the pelvis (abdominopelvic region) was obtained by using Siemens Healthineers Syngo via Frontier cardiac risk assessment. Regression models were used to identify the optimal single-slice in different gender for estimating VAT volume. Statistical significance was established at P < 0.05. Results: Total of 311 Chinese participants including 179 men [age, 55.1±14.9 years; body mass index (BMI), 24.2±3.2 kg/m2; total VAT volume, 2482.6±1276.5 mL] and 132 women [age, 54.3±14.9; BMI, 23.5±2.9; total VAT volume, 1761.5±876.4]. Pearson's correlation analysis revealed a strong association between the VAT area and total abdominopelvic VAT volume at the hilum of the kidney in both men (r=0.938, P<0.001) and women (r=0.916, P<0.001). Adjust for covariates including age, BMI, and waist circumference make a relatively small effect on predicting the total VAT volume. Conclusions: Measurement of cross-sectional areas at the hilum of the kidney in both genders showed a strongest relation to TVAT volume. Our results may provide an identifiable and valuable axial landmark for measuring visceral adipose tissue in clinical practice.